Reconfigurable computing: architectures, tools and applications 7th international symposium, ARC 2011, Belfast, UK, March 23-25, 2011 : proceedings - ARC (Symposium) 2011 Belfast, Northern Ireland); Koch, Andreas 1970 October 1.; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the refereed proceedings of the 7th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2011, held in Belfast, UK, in March 2011. The 40 revised papers presented, consisting of 24 full papers, 14 poster papers, and the abstracts of 2 plenary talks, were carefully reviewed and selected from 88 submissions. The topics covered are reconfigurable accelerators, design tools, reconfigurable processors, applications, device architecture, methodology and simulation, and system architecture.
International conference proceedings.
Keywords: Adaptive computing systems -- Congresses; Computer architecture -- Congresses; Electronic books